Social dividends of migrants: the case of Ukrainian transnational migration - Tolstokorova, Alissa V. (Ревија за социјална политика/Journal of Social Policy, 2013)
The key objective of this paperis to study „social transfers“ of migrants and their impact on daily life of Ukrainian transnational families. The paper argues that for migrants themselves, in contrast to members of their families, it makes sense to speak about „social dividends“ (SD) rather than „social transfers“, understanding them as an added social value of migrancy in the form of non-monetary capital earned from labour migration: social, ethical, cultural, educational, linguistic, civic, etc., used for personal development and wellbeing, but not always sent or brought back home. The paper offers rationale for the distinction between social transfers and social dividends and identifies the inventory of SD, covering personal development SD, cultural-esthetic and spiritual SD, world-view and civic SD, SD of healthy way of life and dividends of gender equality.
Keywords: migration; dividends; Ukraine